Contribution of collaborative project performance to corporate performance in engineering, procurement, and construction (EPC) companies - Syarifudin, Ichsan; Wibisono, Dermawan (2010)
Main purpose of this study is to explore relationships between collaborative supply chain to project performance measures and the contribution of these measures to corporate performance measures in engineering, procurement, and construction (EPC) industry. Collaborative supply chain is useful due to the fact that EPC projects require multidiscipline capabilities, but it is also challenging because of the short term contractual relationships among parties in the collaboration. The existence of EPC contracting companies is important to support the development of infrastructure projects in developing countries.Integrated scope and concurrent project cycle development within EPC contract enable the projects to be developed in a more timely and efficient manner. Contribution of project performance to corporate performance in this industry plays a critical role to maintain sustainable capabilities and growth of an EPC company. A series of interview and survey will be undertaken to acquire information from executives in EPC companies regarding their perception on performance measures of projects and how these measures may support the corporate performance. Constructs emerge from the interviews, will be compared with a predetermined conceptual constructs based on previous research and references. Result of this research may be used as the basis for defining the EPC companies’ corporate performance objectives as a function of collaborative project performance measures. The finding may also be used in assessing the capability of EPC companies to cope with the challenge of accelerated infrastructure development in developing countries. Although a considerable number of construction companies have been developing an EPC division or subsidiary in the past five years, the number of established EPC contractors operating in Indonesia is very limited (less than twenty companies). This limited number of EPC companies implies that data collection activity in this research should consider the ability to represent the industry characteristics.